The level of financial literacy among poor – methodological and empirical results - Potocki, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
One of the methods which help to decrease the level of vulnerability to poverty and social exclusion is the raise the level of financial literacy among poor households. However, to do this effectively one needs to possess the reliable measurement tool, particularly adopted to intellectual capacities of the poor. Unfortunately there is a lack of such tests available in scientific literature. In the light of the current constraints, in author’s opinion, one needs to construct financial literacy test dedicated to poor using evolutionary approach. That is, the ones which not only tests financial literacy but also numeracy, statistical and risk literacy. In authors opinion, the statistical and risk literacy is much more important and more universal then financial literacy. To prove that point author positively verify following thesis “Risk literacy is effective predictor of financial literacy level, especially among poor and vulnerable to poverty population (exogenously and endogenously)”. The author’s study contribute to dynamically developing, interdisciplinary field of research devoted to household finance, especially to financial decisions under poverty and microeconomics of poverty. The structure of the article support formulated goals. The research method was applied to answer the research questions.